Kepemimpinan Emosional sebagai Faktor Kunci dalam Pengambilan Keputusan Pendidikan dan Peningkatan Kualitas Pembelajaran - Muslim, Bukhori; Kunta, Ittaqillah Haitsuma; Baharun, Hasan (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to examine the role of emotional leadership in educational decision-making and improving the quality of learning at MA Miftahul Ulum Banyuanyar Lor, Probolinggo Regency. This study was chosen by considering the socio-economic diversity of students that can affect the learning process at the madrasah. The method used is descriptive qualitative with a case study approach, where data was collected through in-depth interviews with the principal, vice principal for curriculum, three educators, two students, and two parents of students. Observations were also conducted to directly see the emotional interactions that occur in the educational process. The results of the study indicate that the application of emotional leadership, based on the theory of emotional intelligence by Goleman and Salovey, has been shown to improve the quality of learning. Leaders who are able to manage emotions and show empathy succeed in creating an atmosphere that supports learning, motivates educators, and increases students' enthusiasm for learning. However, challenges related to students' socio-economic conditions that affect their emotional conditions remain an important concern in educational management. In conclusion, the emotional leadership that is applied has had a positive impact on the quality of education. Therefore, it is important to continue to develop emotional intelligence at the educational leadership level in order to improve the quality of learning at the madrasah.